E-215 Rotational angiography complicated by aneurysm rerupture: a case series. (4th August 2020) - Nistal, D; Wei, D; Mascitelli, J; Shoirah, H; Starke, R; Levy, E; Howington, J; Mocco, J; Oxley, T
Abstract : Introduction: Digital subtraction angiography (DSA) is considered the gold standard for diagnosing intracranial aneurysms. In cases of aneurysmal subarachnoid hemorrhage (aSAH), 3DRA has become standard of care to detect aneurysms and to plan treatment in cases with inconclusive noninvasive imaging. Rerupture during angiography with contrast extravasation is a rare but devastating complication and has a mortality of 50% to 80%. In this case series, we report our experience of aneurysm rerupture as a complication of 3DRA for aSAH. Methods: The electronic medical records of eight patients across four separate institutions who underwent 3DRA for evaluation of aneurysm after aSAH were reviewed. Data from patient medical charts and their angiographic procedures were reviewed to assess both clinical and angiographic outcomes. Overall case descriptions and patients' histories were reviewed and described in detail. Results: Of the eight cases reviewed, the mean aneurysm size was 9.7±5.5 mm and the mean Hunt Hess and modified Fisher Score on arrival were 3.5±0.96 and 3.25±0.83 respectively. Injection rate, injection volume, and pressure were 3.6±1.4 mL/s, 21±2.1 mL, and 488±124 psi. Inpatient mortality after aneurysmal rerupture was 37.5% (n=3), with 37.5% (n=3) requiring EVD placement and 50% (n=4) requiring craniectomy. Conclusion: This is the first series to report aneurysm rerupture as a complication of 3DRA. Rerupture during 3DRA is a devastating complication that commonly led to patient mortality in our series. Future studies will be needed to further elucidate characteristics of patients associated with 3DRA complications and to compare 3DRA complication rates with other aSAH diagnostic modalities. Disclosures: D. Nistal: None. D. Wei: None. J. Mascitelli: None. H. Shoirah: None. R. Starke: None. E. Levy: None. J. Howington: None. J. Mocco: None. T. Oxley: None.